Variation in object marking of Biblical Hebrew verbs: a preliminary syntactic analysis - Kehrer, Jonathan Stephen (University of the Free State, 2021)
Biblical Hebrew exhibits considerable variation in the syntax of how object/complements appear with verbs. For example, a writer could use a direct object without any additional particles or prepositions, a direct object marked with the particle ’et, or a direct object marked with a pronominal suffix, either on a verb or on the particle ’et. A writer could also mark indirect objects with prepositions, but prepositions may also introduce the direct objects of some verbs. Biblical Hebrew grammars have offered a variety of explanations for these various constructions, but there is little agreement on the terms of reference, syntactic pattern, or semantic purpose for the variation. Recent studies have allowed for advancements in this field of study, including Muraoka’s contribution to understanding verb complementation (1979), Khan’s work on the particle ’et (1984), Bekins’ extensive treatment of object marking within Biblical Hebrew from the perspective of differential object marking (2014), and Garr’s discussion of bound and free pronominal objects that serve as direct objects (2015). Differential object marking is a promising paradigm to process variation in how object/complements appear with Biblical Hebrew verbs. However, none of these studies has examined comprehensively from a linguistic viewpoint all the issues in the variation as described here; each study has focused only on specific lexical verbs, the particle ’et or the use of pronominal suffixes. In addition, there has not been a comprehensive linguistic examination of variation in how object/complements appear with verbs in a specific section of the Biblical Hebrew corpus. This study utilises linguistic theory, specifically generative grammar, linguistic typology, and complexity thinking, to analyse the syntax of how object/complements appear with verbs within the Torah (Pentateuch) of the Hebrew Bible (Old Testament). Within this limited but extensive corpus, the study analyses a small set of roots within Biblical Hebrew that express variation in how the object/complement appears, namely, ’kl “to eat,” nkh “to strike,” škb “to lie down,” and šm‛ “to hear.” The study examines each root for patterns of variation in connection with crosslinguistic typologies of differential object marking, including uses of the root in varying conjugations. The linguistic analysis encompasses syntax, grammatical information, definiteness, word order, the textual source, and factors that influence information structure. The study examines asymmetric differential object marking, both for the object/complement without any particles or prepositions and the object/complement with the particle ’et and for the object/ complement pronominal suffix connected to a verb and the object/complement pronominal suffix connected to the particle ’et. It concludes that there is a direct correlation between high information structure and the presence of the particle ’et on an object/complement. While the identifying elements of high information structure are different for pronominal suffixes, the correlation remains for both the object/complement and the object/complement pronominal suffix. The study also analyses symmetric differential object marking in Biblical Hebrew, noting the variation between the presence and absence of the preposition. It concludes that this variation is attributable to a combination of factors that are different for each root. Finally, this study analyses the Late Biblical Hebrew texts of Esther, Ezra, and Nehemiah to compare the differential object marking in this corpus with the differential object marking of the Torah. A better understanding of the patterns and purposes for variation in how object/complements appear in Biblical Hebrew can provide important information across the spectrum of Hebrew studies. The connection to high information structure can allow for a more consistent and linguistically-grounded basis for discussions in Hebrew grammars of the variation with how object/complements appear. It also can provide biblical exegetes and translators with a means to interpret and translate complex texts, constructions, and idioms.
Dissertation (M.A. (Hebrew))--University of the Free State, 2021
Keywords: Biblical Hebrew; Syntax; Object; Complement; Adjunct; Differential object marking; Valency; Prepositional object; Definite direct object marker; Information structure; Complexity thinking